Travel Location Sequence Recommendation From User’s Point of Interest - Laddha, Shree; Aote, Shailendra (International Journal of Engineering and Technology, 2018)
The major objective of any Travel Recommendation System is to recommend its users to visit the most suitable place in according to the selected location. We present this system of travel recommendation from the experiences of the previously visited users of that location. Apart from the existing systems, our approach not only limited to users traveling interest but also recommends a travel sequence. Our sys-tem also suggest best visiting time, most suitable season, preference of visiting the nearby places and traveling route to reach to your desired location. Here the user can create his friend list and can share his experience of visit to his friends. This user given experience is taken as a feedback by the system to update his recommendations.